Remedition of Organic Pollutan’s in the Wastewater of Rubber by Biosand Filter Media and Water Plants (Echinodorus palaefoliu and Limmnocharis flava) for Media of Fish Life - Lestari, Yeni; Hasbi, M.; ', Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted from February-Apryl 2014 at PT. RiauCrumb Rubber Factory of Pekanbaru, in the road Kelurahan Meranti PandakKecamatan Rumbai. It’s was aims to understand the effectiveness of biosand filtermedia and phytoremediation concept in remediation organic pollutans content inliquid wastewater of rubber for media of fish life. Sampling of BOD5 and CODwere taken in 5 place with interval every 10 days during 2 months for 4 times andanalyzed in departement public of laboratory. Liquid wastewater of rubber usingof 8 reactor units. Each other 2 reactor units to biosand filter media of control andother combined biosand filter with water plants have can reducing organicpollutans. BOD5 of primary Concentration about 387-465,3 mg/l and the end24,3-6,29 mg/l with effectivenesses 89,07-98,73%. While that COD about 710-846,6 mg/l and the end 44,3-45,8 mg/l with effectivenesses 80,39-96,47%.Altough to other parameter such as temperature about 29-310C, pH 6 and DOabout 3,5-3,83 mg/l can support for media of fish life. Percentage of survival ratefor Esomus sp and Pangasius pangasius 100% altough Oreochromis nilothicus93,75-100%. It’s reached standart quality of KEP-51/MENLH/10/1995.Keyword : Biosand filter media, phytoremediation, wastewater